2018
DOI: 10.1039/c8cc01009a
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of shorter and longer trimethyllysine analogues by epigenetic reader proteins

Abstract: Histone N-lysine methylation is a widespread posttranslational modification that is specifically recognised by a diverse class of N-methyllysine binding reader proteins. Combined thermodynamic data, molecular dynamics simulations, and quantum chemical studies reveal that reader proteins efficiently bind trimethylornithine and trimethylhomolysine, the simplest N-trimethyllysine analogues that differ in the length of the side chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…4c). The stronger interaction between the quaternary ammonium cation with Trp28 has been previously observed for D-Kme3, trimethylornithine and trimethylhomolysine 29,31 . We also examined the distance calculated from the N + atom of H3K4me3 to the 5-and 6-membered rings of the Trp18/Trp28, 5F-Trp18/5F-Trp28, 6F-Trp18/6F-Trp28, and 5,6diF-Trp18/ 5,6diF-Trp28 side chains ( Supplementary Figs.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…4c). The stronger interaction between the quaternary ammonium cation with Trp28 has been previously observed for D-Kme3, trimethylornithine and trimethylhomolysine 29,31 . We also examined the distance calculated from the N + atom of H3K4me3 to the 5-and 6-membered rings of the Trp18/Trp28, 5F-Trp18/5F-Trp28, 6F-Trp18/6F-Trp28, and 5,6diF-Trp18/ 5,6diF-Trp28 side chains ( Supplementary Figs.…”
Section: Resultssupporting
confidence: 69%
“…aromatic cages: 5F-Trp18/5F-Trp28, 6F-Trp18/6F-Trp28, and 5,6diF-Trp18/5,6diF-Trp28. Adopting a recently described molecular mechanics-based approach 29,31 , the four systems were solvated in a 10 Å truncated octahedral box of TIP3P water 32 , neutralised explicitly with either sodium or chloride ions, and simulated for 100 ns using the Amberff12SB force field. In all cases of fluorinated KDM5A, the trimethyllysine side chain of H3K4me3 occupies the aromatic cage throughout the simulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with earlier binding studies on different binding proteins for trimethyllysine and trimethylthialysine [24], and differ from recent findings showing that binding of BPTF PHD leads to a much larger decrease in binding affinity (~13-fold) when comparing H3K4me3 and H3K C 4me3 [25]. In support of the former observation, we found that even longer trimethylhomolysine is very well recognized by a panel of the same five reader proteins [10], indicating that the slightly longer C-S-C moiety (compared to C-C-C core) does not significantly alter the readout process, supporting the finding that BPTF PHD indeed should recognize trimethylthialysine well.…”
Section: Resultssupporting
confidence: 89%
“…To gain a better understanding of the exact role of lysine methylation in epigenetics, it is important to develop novel chemical tools for studying the molecular mechanisms that govern the molecular recognition of methylated lysines by reader proteins. An installation of chemically modified methylated lysine analogues into histone proteins [7] and histone peptides [8][9][10][11] has been a valuable method to study how changes in structure affect the association with reader proteins. In addition, a variety of methods have been developed to incorporate unnatural amino acids in both histone proteins and peptides, notably by auxotrophic expression systems [12] or employing the amber stop codon (TAG) [13].…”
mentioning
confidence: 99%
“…5 Recent work using histone peptides revealed that tuning the chemical structure of the trimethyllysine enabled a better understanding of the nature of biomolecular recognition by epigenetic readers. [6][7][8][9] Among examined trimethyllysine analogs, the cysteine-derived trimethyllysine (K c me3) appears to be recognized by epigenetic reader proteins with similar affinity as the natural trimethyllysine, thus making it the closest mimic known to date ( Figure 1d). 10 Site-specific introduction of unnatural Kme3 analogs into intact histone proteins remains a challenge, and among others contributes to incomplete understanding of the role of lysine methylation on the nucleosome structure and function ( Figure 1a).…”
mentioning
confidence: 99%